2014
DOI: 10.1186/1477-7819-12-329
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant bevacizumab and chemoradiotherapy in locally advanced rectal cancer: early outcome and technical impact on toxicity

Abstract: BackgroundWe aimed to evaluate early clinical and pathological results for treating locally advanced rectal cancer with bevacizumab and neoadjuvant concurrent chemoradiotherapy using the technique of prone-position volumetric modulated arc therapy and to compare the toxicity of volumetric modulated arc therapy with that of supine-position four-field box radiotherapy.MethodsTwelve patients with stage IIA to IVA rectal adenocarcinoma, treated with neoadjuvant concurrent chemoradiotherapy (45 Gy in 25 fractions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…The initial database search and manual screening of references retrieved 9987 records, of which 6491 were removed as duplicates, leaving 3496 records which proceeded on to title and abstract screening. 39 potential candidates underwent full-text review, of which 27 [ [10] , [11] , [12] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ] were adequate for inclusion, with 12 studies deemed inadequate for various reasons shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial database search and manual screening of references retrieved 9987 records, of which 6491 were removed as duplicates, leaving 3496 records which proceeded on to title and abstract screening. 39 potential candidates underwent full-text review, of which 27 [ [10] , [11] , [12] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ] were adequate for inclusion, with 12 studies deemed inadequate for various reasons shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of note, among the eligible studies, five [ 5 , 11 , 17 , 18 ] explored the role of TNT. Concerning the countries/districts where these trials were conducted, seven [ 16 , 17 , 19 , 22 , 30 , 33 , 35 ] were in Japan, five [ 10 , 14 , 37 , 41 , 42 ] in the United States of America, four in China (two [15] , [18] in the mainland, two [21] , [32] in Taiwan), four [12] , [29] , [31] , [34] in Spain, two [ 38 , 43 ] in Italy, one [11] in France, one [36] in Germany, one [40] in Greece, one [39] in Slovenia, and one [20] in the United Kingdom. The detailed baseline characteristics and data regarding endpoints of interest from the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 studies were ultimately included, after ruling out 16 ineligible investigations which failed to meet the inclusion and exclusion criteria for this meta‐analysis. The included studies consisted of 21 for the VEGF inhibitor, bevacizumab , and 11 for EGFR inhibitors (eight for cetuximab , one for nimotuzumab and two for panitumumab ). These included one randomized clinical trial (RCT) and three clinical controlled trials (CCT) , but we only analyzed cohorts which tested the addition of targeted agents to their neoadjuvant therapy regimens for this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These included one randomized clinical trial (RCT) [54] and three clinical controlled trials (CCT) [34,53,55], but we only analyzed cohorts which tested the addition of targeted agents to their neoadjuvant therapy regimens for this meta-analysis. There were also two bevacizumab-relevant studies [22,52] consisting of two arms with bevacizumab in their neoadjuvant regimens, and we included all four cohorts for the meta-analysis. Additionally, there was one study [49] consisting of two cohorts testing addition of bevacizumab, one in the neoadjuvant setting and the other in the postoperative setting, and we included only the former.…”
Section: Study Selection and The Characteristics Of Included Studiesmentioning
confidence: 99%
“…Применение химиотерапии в режиме консолидации после завершения химиолучевой терапии и немногочисленные опубликованные по этому направлению сообщения демонстрируют высокие результаты по уровню достижения полного лечебного патоморфоза [9,10,12]. Лечебный патоморфоз и патологическая стадия опухолевого процесса тесно связана с отдаленными результатами лечения [3,5,36,19,29]. ретроспективный анализ Capirci et al результатов лечения 566 пациентов, у которых был достигнут полный лечебный патоморфоз в опухоли, показал увеличение до 85% и 90% пятилетней безрецидивной и общей выживаемости, а также снижение локальных рецидивов до 1,6% и отдаленных метастазов до 8,9% [3].…”
Section: материалы и методыunclassified